Desarrollo e implementación de una aplicación web y móvil aplicando prácticas ágiles para la administración de cobranzas de patentes comerciales pertenecientes al Gad Municipal del Cantón Muisne - Flores Santos, Katherine Margoth (2022)
The purpose of this technological proposal is innovation with the development of software in the Municipal Decentralized Autonomous Government of Muisne, in which several studies were carried out allowing the design and development of a web and mobile application in order to optimize processes. For the execution of this technological proposal, agile methodologies such as SCRUM and MOBILE-D were adapted, which are agile development models that focus on exchange, communication and reducing intermediate components. This has a great capacity to respond to changes, which are not understood as a problem but as something necessary for the product to be better and meet customer requirements. Through bibliographic research, the tools and the programming language were chosen that allow for optimal system performance, it is of great importance to carry out an analysis of the application requirements to achieve the implementation of the system, where it allows the integrity of the data. The elaboration of the system uses current technical tools such as the development environment called Android Studio with respective libraries that intervene in the development of the requirements. This helps refine native mobile apps for devices. Equipped with the Android operating system, version 5 or later. Similarly, the development of the site is done using the Python programming language and its Django framework, and several of its libraries are already included. Proper and safe handling when used for pinpointing. Tests were carried out in order to verify that the web and mobile application work correctly with the entry and modification of data.